Scale and Spatial Distribution of Optical Aberrations Associated with Tear Break-up - Himebaugh, Nikole L. (2012)
PURPOSE: We examined the spatial correlation between tear break up (TBU) and the associated optical anomalies on multiple spatial scales. METHODS: Five subjects refrained from blinking while the time course and patterns of TBU were sequentially observed using fluorescein (FL), retroillumination (RI), and Shack-Hartmann (SH) aberrometry. Wavefront error maps were developed using Zernike polynomials, as well as local zonal analysis of measured wavefront slopes. The difference between these maps reveals the presence of very high order aberrations missed by standard modal fitting methods. Size of SH spots was also quantified to estimate optical perturbations on a microscopic scale. The spatial correlation between TBUand optical aberrations was also computed. RESULTS: Degradation of the tear film increased wavefront aberrations over all spatial scales measured. Consistent with tear thinning, blink suppression induced an irregular pattern of phase advances in regions of TBU. SH spot size also increased in regions of TBU, which indicates the presence of optical aberrations on a scale smaller than individual lenslets. CONCLUSIONS: The optical signature of TBU caused by blink suppression is a combination of wavefront aberrations on macroscopic and microscopic scales due to nonuniform tear film thinning and possible exposure of a rough epithelial surface. Localized optical 2 defects correspond temporally and spatially with TBU revealed by FL and RI. In addition to gross wavefront aberrations, scatter develops in areas of TBU that will further contribute to image degradation and visual disturbances following TBU.